The Fair Funding Review: Is a fair assessment of councils' spending needs feasible? - David Phillips; Tom Harris (Institute for Fiscal Studies (IFS), 2018)
English local government finance is part way through a series of major changes that will see its focus shift from being based on redistribution according to spending needs, towards more emphasis on providing financial incentives to tackle needs and increase local revenue-raising capacity. In this context, the government is undertaking a "Fair Funding Review". This is aimed at designing a new system for allocating funding between councils. In particular, the Review will update and improve methods for estimating councils' differing abilities to raise revenues and their differing spending needs. The government is looking for the new system to be simple and transparent, but at the same time robust and evidence based. This paper focuses on the issues that arise in assessing the spending needs of different councils. A companion paper looks at the assessment of revenue-raising capacity, and discusses options for the overall design of the new funding system. [...]
Keywords: 330